Cell-Based Phenotyping Reveals QTL for Membrane Potential Maintenance Associated with Hypoxia and Salinity Stress Tolerance in Barley - Gill, Muhammad B.; Zeng, Fanrong; Shabala, Lana; Zhang, Guoping; Fan, Yun; Shabala, Sergey; Zhou, Meixue (Frontiers in Plant Science, 2017)
Abstract: Waterlogging and salinity are two major abiotic stresses that hamper crop production world-wide resulting in multibillion losses. Plant abiotic stress tolerance is conferred by many interrelated mechanisms. Amongst these, the cell’s ability to maintain membrane potential is considered to be amongst the most crucial traits, a positive relationship between the ability of plants to maintain highly negative membrane potential and its tolerance to both salinity and waterlogging stress. However, no attempts have been made to identify quantitative trait loci (QTL) conferring this trait. In this study, the microelectrode MIFE technique was used to measure the plasma membrane potential of epidermal root cells of 150 double haploid (DH) lines of barley (Hordeum vulgare L.) from a cross between a Chinese landrace TX9425 and Japanese malting cultivar Naso Nijo under hypoxic conditions. A major QTL for the membrane potential in the epidermal root cells in hypoxia-exposed plants was identified. This QTL was located on 2H, at a similar position to the QTL for waterlogging and salinity tolerance reported in previous studies. Further analysis confirmed that membrane potential showed a significant contribution to both waterlogging and salinity tolerance. The fact that the QTL for membrane potential was controlled by a single major QTL illustrates the power of the single-cell phenotyping approach and opens prospects for fine mapping this QTL and thus being more effective in marker assisted selection.